(Table 1) Consolidation characteristics and physical properties for DSDP Legs 56-57 Holes - Les E Shephard; William Bryant (PANGAEA, 1980)
Consolidation characteristics of marine sediments have been determined for several different geologic provinces (cf. Hamilton, 1959, 1964; Keller and Bennett, 1973; Trabant, 1977; and Shephard et al., 1978). These data have been used to enhance interpretation of sediment processes; to develop density, porosity, permeability, and depth relationships; to predict excess pore water pressures; as well as to determine the amount of sediment originally present before consolidation. With the inception of plate tectonic theory several geologic and geotechnical investigations have been performed to aid in delineating those processes associated with fore-arc slope development in various trench systems (cf. Lee et al., 1973; Carson et al., 1974; Seely et al., 1974; Bouma and Moore, 1975; Trabant et al., 1975; Moore and Karig, 1976; and Seely, 1977). Many of these studies have included consolidation testing. Lee et al. (1973) tested overconsolidated sediments below 300 meters at DSDP Site 181 (Aleutian Trench). Trabant et al. (1975) reported highly overconsolidated sediments below 397 meters at DSDP Site 298 (Nankai Trough). Carson (1977) discussed overconsolidated mudstones dredged from the Cascadia Basin. Each of these studies suggests the state of overconsolidation results from tectonically induced stress, deformation, and uplift. The ensuing discussion will describe consolidation test results from samples obtained in the Japan Trench province during DSDP Legs 56 and 57.
Supplement to: Shephard, LE; Bryant, W (1980): Consolidation characteristics of Japan Trench sediments. In: Scientific Party, Initial Reports of the Deep Sea Drilling Project, 56/57 (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 56-57, 1201-1205, https://doi.org/10.2973/dsdp.proc.5657.152.1980